THE TABOO WORDS ANALYSIS IN "DAISY JONES & THE SIX" NOVEL - Fadhila Ananda Putri Panigoro; Suci Budiwaty (Journal of Language and Literature, 2022)
Language and society are strongly intertwined. Society needs language to be connected, and language needs society to use it properly. The study that correlates with language and society is taboo words. Taboo words are the restriction or avoidance of spoken and written words in any society that is harmful to its members because they would give them discomfort and humiliation. The research focused on the taboo words, primarily about the types and functions in the novel entitled Daisy Jones & The Six by Taylor Jenkins Reid. The objectives of this research were to find out the types and the functions of taboo words in Daisy Jones & The Six novel. This research used the qualitative method since the data are in the form of quotations and descriptions in a thorough description involving the researcher’s interpretation. The result of the research showed that there were 123 data of taboo words categorized into four types, consisting of 68 data of Obscenity, 30 data of Profanity, 17 data of Epithets, and 8 data of Vulgarity. The mentioned data of taboo words were categorized into five functions, those were 61 data of Descriptive-Evaluative, 43 data of Anger and/or Frustration, 9 data of Surprise, 8 data of Sarcastic Irony or Insults, and 2 data of Joking.